INTERVENE: BYSTANDER INTERVENTION TRAINING FOR STUDENTS - Swank, Aaron (My University, 2017)
In February of 2017, I met with Jenny Yuen, MPH, CHES with the desire to be involved in raising awareness of sexual assault among students at Kansas State University. We began collaboration on a project with the goal to develop a bystander intervention training workshop to empower students to act in the case of an alcohol emergency, observation of an unhealthy relationship, and to prevent sexual assault. I worked with a small group of three undergraduates to build and deliver Intervene: Bystander Intervention Training for Students in April 2017. This program included a discussion of data collected from a mandatory Alcohol and Sexual Assault Prevention course which every student must complete at the beginning of each Fall semester. This discussion was followed by intervention skills training which featured videos of young actors portraying scenarios in which many college-aged men and women may find themselves throughout their college careers. These videos helped illustrate appropriate action to take to keep peers safe during an alcohol emergency, how to help a close friend escape an unhealthy relationship, and how to safely intervene to prevent sexual assault at a house party. The details of the Intervene programs as well as my involvement in the development of this project as part of my field experience are detailed in the following report.
Keywords: Sexual assault; alcohol emergencies; healthy relationships; bystander intervention; ASAP